2014
DOI: 10.1097/iop.0000000000000013
|View full text |Cite
|
Sign up to set email alerts
|

Excision and Delayed Reconstruction With Paraffin Section Histopathological Analysis for Periocular Sebaceous Carcinoma

Abstract: Excision and delayed reconstruction using paraffin section histopathological analysis are in widespread use for the management of basal cell carcinomas in the periocular region. While some authors advocate the use of Mohs' micrographic surgery in patients with SC, this technique has been questioned due to the possible misinterpretation of subtle intraepithelial pagetoid spread with frozen section analysis. To preserve the function of the eyelid and ease of reconstruction, it is important to try and preserve as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 23 publications
0
16
0
2
Order By: Relevance
“…It is estimated that 41–80% of SGC have associated pagetoid spread [ 14 ]. Contemporary studies report local tumour recurrence in 12–25% of patients [ 1 , 5 , 10 , 12 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is estimated that 41–80% of SGC have associated pagetoid spread [ 14 ]. Contemporary studies report local tumour recurrence in 12–25% of patients [ 1 , 5 , 10 , 12 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Local anaesthesia was obtained with a subcutaneous injection of 0.5% bupivacaine with adrenaline 1 in 200000. Our technique of full thickness excision with delayed reconstruction has been previously described [ 12 ]. As well as primary lesions, 8–10 conjunctival mapping biopsies were also taken from all quadrants of bulbar and tarsal conjunctiva and sent separately on microsponge pieces, in formalin with a diagram (see Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Although SC clinical features have been reported and various treatment modalities have been performed, delayed diagnosis with metastasis to regional lymph nodes and distant organs often occurs in 3–41% of all patients with eyelid SCs (While et al. ). Consistent with previous reports, our consecutive study showed that 21.9% (9/41) of the patients experienced nodular metastasis and 2.4% (1/41) showed metastasis to distant organs, involving five patients who twice experienced recurrence, followed by frozen section procedures before metastasis, and one patient who died of lung metastasis 12 months after a frozen section + unilateral neck dissection + unilateral radical parotidectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy, cryotherapy, topical chemotherapy, amniotic membrane grafting, flap reconstruction, and other techniques are followed by surgical excision to achieve the best treatment effect. 5 , 13 , 16 , 37 , 38 …”
Section: Introductionmentioning
confidence: 99%